Faktor-Faktor yang Mempengaruhi Sikap dan Intensi Pengurus Koperasi Untuk Menggunakan Platform Layanan Keuangan Digital di Kota Bandung - Zahra, Hana Al; Febrian, Erie; Amar, S.C. Djen (Jurnal Manajemen, 2019)
This study aims to analyze the factors that influence the attitudes and intentions of Indonesian cooperatives, especially in the city of Bandung in using digital financial service platform. The test conducted in this study is to examine the relationship between Perceived Usefulness, Perceived Ease of Use, Knowledge, Trust and Perceived Risk on Attitudes and Intentions, which are tested partially and simultaneously. The method of analysis of this research uses quantitative and qualitative approaches in the form of descriptive - verification. Hypothesis testing uses Partial Least Square (PLS) analysis with a sample of 100 respondents from 70 cooperatives conducting savings and loan activities in the city of Bandung. The results of the analysis of research data indicate that Knowledge and Trust have a significant positive effect on Attitude and Intention. Perception of Use only has a significant positive effect on attitude. While Perception of Ease and Risk does not have a significant positive effect on Attitude and Intention. The results indicate that Knowledge and Trust have a significant positive effect on Attitude and Intention. Perceived Usefulness only has a significant positive effect on Attitude. While Perceived Ease of Use and Risk does not have a significant positive effect on both Attitude and Intention. Simultaneously all variables X explain 77.9% of Attitude and 86.5% of Intention.